Political communication as television news: Party-produced news of the Sweden Democrats during the 2022 election campaign - Ekman Mattias; Widholm Andreas (Nordicom Review)
Political communication has taken new and complex forms within the contemporary hybrid media system. In this article, we examine how political campaigning that draws on television news forms utilises the increasingly blurred boundaries between news journalism and politics online. We assess the digital television news channel Riks, which during the 2022 national election was operated by the Sweden Democrats party and distributed via YouTube. Deploying a mixed-methods approach, we analysed all videos published by Riks four weeks prior to the election. Results show that Riks blends descriptive, interpretative, and outrage genres, and strategically frames the most important political issues of the election campaign in favour of the party’s policies. Hence, the study contributes to political communication scholarship by emphasising how news has become an integral part of strategic party communication, challenging established scholarly conceptualisations of alternative media and hyperpartisan news.